Intake of slow-digesting carbohydrates is related to changes in the microbiome and its functional pathways in growing rats with obesity induced by diet - Plaza-Díaz, Julio; Manzano, Manuel; Ruiz-Ojeda, Francisco Javier; Giron, Maria D.; Salto, Rafael; López-Pedrosa, Jose M.; Santos-Fandila, Angela; Garcia-Corcoles, Maria Teresa; Rueda, Ricardo; Gil, Ángel (Frontiers in Nutrition, 2022)
Childhood obesity is the main driver of insulin resistance and contributes to future comorbidities in adulthood. High-calorie diets and lack of physical activity play a role in the development of metabolic diseases, and though the energy density of food is one of the main obesogenic factors; indeed, food quality rather than the quantity of the different macronutrients is desirable. The present study aimed to investigate the effects of changing the quality of carbohydrates from rapidly to slowly digestible carbohydrates on gut microbiota composition and functional pathway profiles in growing rats fed a high-fat diet (HFD). Growing rats were fed on an HFD containing carbohydrates with different digestion rates: an HFD containing rapid-digesting carbohydrates (OBE group) or slow-digesting carbohydrates (ISR group), for 4 weeks. A non-obese group (NOB) was included as a reference and rats were fed on a rodent standard diet (AIN93G). The composition of gut microbiota was analyzed by 16S rRNA-based metagenomics; a linear mixed-effects model (LMM) was used to determine the abundance changes from baseline to 4 weeks of treatment, and functional pathways were identified. The groups showed comparable gut microbiota at the baseline. At the end of the treatment, animals from the ISR group exhibited differences at the phylum levels (decreasing the diversity of Fisher index, and Firmicutes, and increasing the Pielou's evenness and Bacteroidetes); at the genus level by increasing Alistipes, Bifidobacterium, Bacteroides, Butyricimonas, Lachnoclostridium, Flavonifractor, Ruminiclostridium 5 and Faecalibaculum, and decreasing Muribaculum, Blautia and Ruminiclostridium 9. Remarkably, relative abundances of genera Tyzzerella and Angelakisella were higher in the OBE group compared to NOB and ISR groups. Furthermore, microbiota carbohydrate metabolism pathways such as glycolysis, glucuronic acid degradation, pentose-phosphate pathway, methanogenesis, and fatty acid biosynthesis, among others exhibited higher activities in the ISR group after the treatment. Higher levels of acetate and propionate were found in the feces of the ISR group compared with the NOB and OBE groups. This study demonstrates that the replacement of rapidly digestible carbohydrates for slowly digestible carbohydrates within an HFD improved the gut microbiota composition, which may have a protective effect against the development of metabolic disturbances in obesity.